LEGAL ASPECT OF GEOTHERMAL IN INDONESIA ACCORDING ACT NUMBER 27/2003 - Mohammad Taufik Makarao (VERITAS, 2017)
With the existence of Law Number 27 of 2003 on Geothermal and someimplementing regulations are sufficiently comprehensive so that it will be able toprovide legal certainty for business actors to invest heirs. Based on the data showsthat the potential of geothermal in Indonesia is still large enough that has not beenutilized optimally, it is seen from the geothermal working area in Indonesia. It isrecommended that the government keep improving its role in the effort to socializethe importance of geothermal energy as an alternative that needs to be developed.By developing a defined Geothermal Working Area and a new WKP (estimatedtotal potential of about 13,000 MWe) is expected to achieve geothermal poweravailability of 6000 MWe by 2020. Thus consumption and dependence on fossilenergy in the country will decrease.